Weird Fiction in Britain 1880-1939 - Machin, James (Palgrave Gothic, 2018)
This book is the first study of how 'weird fiction' emerged from Victorian supernatural literature, abandoning the more conventional Gothic horrors of the past for the contemporary weird tale. It investigates the careers and fiction of a range of the British writers who inspired H. P. Lovecraft, such as Arthur Machen, M. P. Shiel, and John Buchan, to shed light on the tensions between 'literary' and 'genre' fiction that continue to this day. Weird Fiction in Britain 1880-1939 focuses on the key literary and cultural contexts of weird fiction of the period, including Decadence, paganism, and the occult, and discusses how these later impacted on the seminal American pulp magazine Weird Tales. This ground-breaking book will appeal to scholars of weird, horror and Gothic fiction, genre studies, Decadence, popular fiction, the occult, and Fin-de-Siècle cultural history. .